Economic conditions of government expenditure on education in higher education system - Andrzej Rozmus; Karolina Cyran (e-Finanse: Financial Internet Quarterly, 2012)
Higher education institutions are an essential, endogenous element of economic development and take part in resolving global issues. Their utilitarian role, however, may be greatly limited as a result of improper ways of financing science and didactics. The prevailing mechanism of financing didactics in public universities in Polish reality does not ensure the effectiveness of deployed resources and only partially bases on competition, thus not generating the stimuli for positive changes. The algorithm on the basis of which the resources are allocated should be modified. It should be based on criteria reflecting changes in social and economic surroundings. It should also comprise mechanisms stimulating competition between universities and enhancing the quality of didactics and science.
Keywords: I21; I22; I28; 330; higher education; financing higher education